De la langue au harcèlement en passant par les systèmes discursifs de discrimination – la construction linguistique du genre - Béatrice Fracchiolla (Corela)
This article deals with the pragmatic issues of the different modes of addressing and designating women in their legitimizing process to be persons like others. It observes and analyses the performative modalities of the treatment of these questions in the institutional, administrative and legal environment which sometimes involves financial sanctions (fines). This is for instance the case, at a global and recognized level, for political parties which do not respect the law on parity. Language and linguistic discrimination against women is an acculturated phenomenon and therefore rendered invisible, which can only be broken in its circularity by making it visible through surveys and analyses of some of these phenomena that make up women’s daily lives. Various analyses of administrative facts and forms that discriminate against women illustrate the necessity and the difficulties of a paradigm shift - namely, indeed, acknowledging the fact that women are human beings like any others.